Specific wavelengths modify the antioxidant system of tomato and cucumber - Escobar-Hernández, Diego Iván; González-García, Yolanda; López-Barbosa, Lorenzo Alejandro; Juárez Maldonado, Antonio (Ecosistemas y Recursos Agropecuarios, 2024)
Light has a positive impact on the regulation of plant development processes. However, evidence suggests that responses to changes in the light spectrum depend on plant species. The objective of this work was to evaluate the effect of supplemental lighting with LEDs on growth, phytochemical synthesis and fruit quality in tomato and cucumber crops. For this, an experiment was established, tomato (Solanum lycopersicum L.) and cucumber (Cucumis sativus L.) plants were grown with supplemental light from 7:00 p.m. to 12:00 a.m. using LED lamps with blue (455 nm), red (660 nm) and far-red light (730 nm). The treatments were the application of the different wavelengths with one (above the canopy) or two lamps (above the canopy and base of the plant), plus a control (T0) without supplementary light. Changes in agronomic parameters, phytochemical content, and fruit quality were evaluated. The results demonstrated an impact on the height of tomato plants, in addition, photosynthetic pigments increased in tomato leaves (18.4 - 29.1%), lycopene in leaves (166.7 - 207.4%) and cucumber fruits (83.2 - 175.5%), and carotenoid compounds in tomato fruits (106.9 – 127.5%). The quality attributes of the fruits such as TSS, pH and EC were also modified. In conclusion, the results showed that light supplementation through LED lamps induces positive responses in tomato and cucumber crops, improving the quality and bioactive compounds of tomato and cucumber fruits.
Keywords: Antioxidants; Carotenoids; Stimulation; LED lamps; Photosyntetic pigments